Productivity enhances benthic species richness along an oligotrophic Indian Ocean continental margin - Mccallum, A.; Woolley, S.; Blazewicz-Paszkowycz, M.; Browne, J.; Gerken, S.; Kloser, Rudy; Poore, G.; Staples, D.; Syme, A.; Taylor, J.; Walker-Smith, G.; Williams, A.; et al. (Wiley-Blackwell Publishing, 2015)
© 2014 John Wiley & Sons Ltd.Aims: Marine soft sediments cover much of the deep ocean and are one of the largest habitats in the world, yet much of our understanding about their diversity is based on sampling in the North Atlantic. The deep-sea benthos provides a simplified environment in which to explore the processes which maintain species richness. Here we investigate the influence of energy and habitat complexity on benthic species richness along an oligotrophic continental margin within the Indian Ocean. Location: The upper continental margin of western Australia (c. 13-35°S, 100-1000m depth). Methods: We examined the species richness of selected polychaetes (Annelida) and crustaceans in sediment grab samples. We used generalized linear models and hierarchical partitioning to examine the relationship and relative importance of temperature, productivity (particulate organic carbon flux, net primary productivity and depth) and habitat complexity (sediment particle size diversity and grain size) on species richness at 51 sites. Results: In contrast to benthic studies in the North Atlantic, we found that species richness was higher on the shelf than on the slope. Species richness was positively correlated with net primary productivity; this relationship was influenced by high species richness in two areas where oceanic mixing is known to enhance primary productivity. Habitat heterogeneity and temperature were less influential. Main conclusion: This study represents one of the first extensive quantitative studies of deep-water benthos in the Indo-West Pacific, and provides further evidence that bathymetric gradients of species richness are variable between regions, probably due to variation in local oceanography and productivity regimes. Our findings provide support for the overriding influence of productivity on species richness, even over relatively small ranges in depth and productivity. As climate change is expected to modify biogeochemical fluxes to the deep seafloor, this is likely to affect the communities of deep-sea fauna.